Seven years of recording from monkey cortex with a chronically implanted multiple microelectrode - Krüger, Jürgen; Caruana, Fausto; Dalla Volta, riccardo; Rizzolatti, Giacomo (Frontiers in Neuroengineering, 2010)
A brush of 64 microwires was chronically implanted in the ventral premotor cortex of a macaque monkey. Contrary to common approaches, the wires were inserted from the white matter side. This approach, by avoiding mechanical pressure on the dura and pia mater during penetration, disturbed only minimally the cortical recording site. With this approach isolated potentials and multiunit activity were recorded for more than seven years in about one third of electrodes. The indirect insertion method also provided an excellent stability within each recording session, and in some cases even allowed recording from the same neurons for several years. Histological examination of the implanted brain region shows only a very marginal damage the recording area. Advantages and problems related to long-term recording are discussed.